The Islamic healing approach to cancer treatment in Malaysia - Suhami, Norhasmilia; Muhamad, Mazanah; Krauss, Steven Eric (IISTE, 2014)
Islamic healing is frequently sought as a choice by Muslim cancer patients in Malaysia. Despite its widespread use, limited documented evidence is available on Islamic healing practice in cancer treatment. Such information gives better insight about Islamic healing in cancer treatment to adjust treatment policies and practices accordingly. The purpose of this study is to understand Islamic healing practice in conjunction with conventional medicine for cancer treatment. A qualitative approach was deemed appropriate in investigating patient perspectives and experiences related to Islamic healing. Sixteen cancer survivors who had received both conventional medicine and Islamic healing during their treatment were identified by referrals from support group members, healers, and friends as participants in the study. The data were collected through semi-structured interviews. Interview data were transcribed verbatim and were analyzed concurrently using the constant comparative method. Islamic healing treatment can be divided by 2 forms; 1) recitation of Quran verses alone and (2) mixed methods, which include the recitation of Quran, herbs and bless water. Islamic healing is structured similar to conventional healing and most Islamic healing occurs in the form of 2 main approaches, although there are minor variations within those approaches.